2008
DOI: 10.1002/uog.5351
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the feasibility of four‐dimensional ultrasound imaging using spatiotemporal image correlation in routine fetal echocardiography

Abstract: Objectives To investigate the feasibility of incorporating spatiotemporal image correlation (STIC) into a tertiary fetal echocardiography program. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 21 publications
5
82
1
1
Order By: Relevance
“…Firstly, the acquisition of eSTIC volumes requires special software which is not available in all ultrasound machines, and it is operator dependent [20]. The electronic 4D probe minimized the influence of fetal movements by shortening the acquisition time, but unfavorable fetal position was still the main reason for eSTIC failures.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the acquisition of eSTIC volumes requires special software which is not available in all ultrasound machines, and it is operator dependent [20]. The electronic 4D probe minimized the influence of fetal movements by shortening the acquisition time, but unfavorable fetal position was still the main reason for eSTIC failures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that high-quality volumes can be obtained in 65% to 90% of a certain population throughout pregnancy. 20,22,42 In this study, after volume acquisition, a rapid preview was performed to determine whether the volume contained all of the information that we needed and the quality was acceptable. If not, this volume was abandoned.…”
Section: Volume Acquisitionmentioning
confidence: 99%
“…[11][12][13] Spatiotemporal image correlation (STIC) is a technique that creates a 4-dimensional (4D) sonographic volume of the fetal heart, 14 from which fetal cardiac images can be obtained in 3 orthogonal planes. [15][16][17] Numerous studies have reported STIC as a useful tool in fetal cardiac function assessment and prenatal diagnosis, [18][19][20] and a recent study reported the use of M-mode STIC in fetal cardiac dimension measurement. 21 However, the accuracy, agreement, and reliability of STIC-based measurements have not been fully investigated yet.…”
mentioning
confidence: 99%
“…If the acquisition is made according to protocol and using static 3D, a fast acquisition with good resolution and minor exposure to artifacts can generally be achieved, but at the cost of losing the functional information included in the heart movement and cine [15] . Some reports address the question of the ability of non-expert operators to acquire good-quality volume datasets of the fetal heart [16][17][18] . It would be logical to assume that with practice and experience, combined with ongoing improvements in image resolution and an expected reduction in the time required to achieve acquisitions, this first essential step in volume ultrasound should become increasingly straightforward.…”
Section: Is It Feasible For a Remote Sonographer To Acquire Good Volumentioning
confidence: 99%
“…In my opinion, two different factors must be taken into consideration prior to any critical analysis of the accuracy of the method. Firstly, operators who are motivated and enthusiastic to learn the acquisition method and correct their technique over time based on feedback from a remote reviewer will produce the good-quality volume datasets so essential for any subsequent successful analysis [5,6,16,17] . Almost 2 decades ago, Sharland and Allan [22] already demonstrated that the enthusiasm and attitude of the physicians involved in fetal heart screening was often reflected in the results.…”
Section: Once a Volume Has Been Acquired And Transmitted Via The Intementioning
confidence: 99%